Slags in Production of Manganese Alloys. Issue 7 (6th March 2013) - Ostrovski, Oleg; Swinbourne, Douglas
Abstract: The paper analyses the equilibrium partitioning of manganese and silicon between slag and alloy during the production of high carbon ferromanganese (HC FeMn) and silicomanganese (SiMn) using FACTSage software. The results of this modeling are compared with industrial and experimental data and used to elucidate the nature of the reduction processes. In production of HC FeMn, molten slag co‐exists with a monoxide phase (Ca, Mg, Mn)O in which MnO is the major constituent. Analysis of industrial data shows that slag and monoxide are close to equilibrium, but manganese slag–metal partitioning is far from equilibrium. It is evident that the rate of MnO reduction from the slag is slower than the rate of MnO dissolution into the slag. A previous laboratory study confirmed that MnO reduction from HC FeMn slag is slow and that equilibrium is not reached. In the production of SiMn, the charge consists of manganese ore, ferromanganese slag, quartzite, and fluxes. Excavation of industrial furnaces has revealed the presence of quartzite in the reaction zone, so there are four condensed phases in the reaction zone; molten slag, molten SiMn alloy, quartzite, and coke. FACTSage modeling showed that during the production of SiMn, manganese, and silicon partitioning between the metal and slag is close to equilibrium at 1600°C. The concentration of silica in SiMn slags is much lower than the silica‐saturation value. It can be concluded that the reduction of silica from these slags is faster than the dissolution of quartzite into the slag. Abstract : The paper analyses the equilibrium partitioning of manganese and silicon between slag and alloy during the production of high carbon ferromanganese (HC FeMn) and silicomanganese (SiMn) in comparison with industrial and experimental data. In production of HC FeMn, manganese slag–metal partitioning is far from equilibrium; in the production of SiMn, manganese, and silicon partitioning between the metal and slag is close to equilibrium at 1600°C.